Meditative Movement as a Treatment for Pulmonary Dysfunction in Flight Attendants Exposed to Second-Hand Cigarette Smoke: Study Protocol for a Randomized Trial - Payne, Peter; Zava, David; Fiering, Steven; Crane-Godreau, Mardi (Frontiers in Psychiatry, 2016)
A study protocol is presented for the investigation of Meditative Movement (MM) as a treatment for pulmonary dysfunction in Flight Attendants (FA) who were exposed to second-hand cigarette smoke (SHCS) while flying before the smoking ban. The study will have three parts, some of which will run concurrently. The first is a data gathering and screening phase, which will gather data on pulmonary and other aspects of the health of FA, and will also serve to screen participants for the other phases. Second is an exercise selection phase, in which a variety of MM exercises will be taught, over a 16-week period, to a cohort of 20 FA. A subset of these exercises will be selected on the basis of participant feedback on effectiveness and compliance. Third is a 52-week randomized controlled trial (RCT) to evaluate the effectiveness of a digitally delivered form of the previously selected exercises on a group of 20 FA, as compared with an attention control group. Outcome measures to be used in all three parts of the study include the six-minute walk test as a primary measure, as well as a range of biomarkers, tests and questionnaires documenting hormonal, cardio-respiratory, autonomic and affective state. This study is registered at ClinicalTrials.gov. Identifier: NCT02612389.